1984
DOI: 10.1901/jeab.1984.41-27
|View full text |Cite
|
Sign up to set email alerts
|

Graded Differential Reinforcement: Response‐dependent Reinforcer Amount

Abstract: After key pecking had been autoshaped, six pigeons were exposed to a condition in which the duration of grain availability at the end of an 8-second trial depended on the number of responses emitted during the trial (0.25-second access to grain per response). This procedure, called correlated reinforcement, alternated across conditions with the automaintenance baseline in which the 8-second trial terminated with a constant 2.5-second access to grain. Two control procedures were run; in both, the reinforcer dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 16 publications
3
27
1
Order By: Relevance
“…The effects of the correlated outcomes used here on overall rates of responding under an FI schedule were not consistent with earlier studies that found that response rates were sensitive to reinforcer magnitude (Dodd, 1980;Gentry & Eskew, 1984;cf. Figure 1) under correlated-schedule outcomes.…”
Section: Effects Of Correlated Contingencies On Fi 8-min Performancecontrasting
confidence: 71%
See 1 more Smart Citation
“…The effects of the correlated outcomes used here on overall rates of responding under an FI schedule were not consistent with earlier studies that found that response rates were sensitive to reinforcer magnitude (Dodd, 1980;Gentry & Eskew, 1984;cf. Figure 1) under correlated-schedule outcomes.…”
Section: Effects Of Correlated Contingencies On Fi 8-min Performancecontrasting
confidence: 71%
“…In behavior-correlated schedules of reinforcement, the amount of each reinforcer is contingent upon some aspect of the subject's performance (Dodd, 1980;Gentry & Eskew, 1984;Hendry, 1962;Hendry & Van-Toller, 1964). Although few investigations of such schedules have been conducted, each has provided evidence that such arrangements can influence behavior in predictable ways.…”
mentioning
confidence: 99%
“…Those relations may be conceived as correlations that vary in terms of degree (high or low) and direction (positive or negative) (Gentry & Eskew, 1984;Logan, 1960). A positive correlation between response frequency and reinforcer magnitude may be established by making larger reinforcer magnitudes dependent on either shorter interresponse times (e.g., Hendry, 1962) or a greater number of responses per interval (e.g., Gentry & Eskew, 1984). Compared to control conditions in which reinforcer magnitude is delivered independently of response frequency, the effects of both these procedures have, of course, been found to be similar: Response rates were higher under correlated conditions than under control conditions.…”
mentioning
confidence: 99%
“…Thus a very high degree of correlation can be established by increasing the magnitude by a given amount for every specified increase in response frequency (Gentry & Eskew, 1984;Hendry, 1962). These two procedures for arranging the degree of correlation between response frequency and reinforcer magnitude have not yet been compared directly.…”
mentioning
confidence: 99%
See 1 more Smart Citation